Identication and Classification of Menoreh Durians Based on Molecular - RAPD Markers - Nandariyah - Nandariyah; Endang - Yuniastuti (Journal of Biodiversity and Biotechnology, 2022)
Menoreh durian is an accessions durian fruit originally from Kulonprogo district, Special Region of Yogyakarta, Indonesia. In the context of proposing Menoreh durian to be a new superior variety, it is necessary to have an identity and position in the molecular genetic group. The aim of the study was to obtain the identity and position of the of Menoreh Durian  in the molecular genetic classification. The wet laboratory experiment was using PCR-based RAPD method. Eleven accessions of durian were identified and characterized then grouped based on molecular analysis which were pink Menoreh and 3 Yellow Menoreh accsessions, Petruk, Sunan, Sukun, Sitokong, Montong, Kani and Aspar. The RAPD method was carried out in stages: DNA extraction, DNA quantity and quality test, amplification, electroforesis, visualization and analysis of results. The RAPD classification of 11 durian accessions , resulted in three groups; namely group I which consisted of Menoreh Kuning, Petruk, Aspar Sunan and Menoreh Jambon; Group II consisted of Montong, Sitokong, and Kani from Thailand; and group III consisted of only Sukun accession. Based on this grouping, Menoreh Kuning dan Menoreh Jambon which were separated from other groups at a genetic distance of more than 0.25 indicated that the accession of Menoreh Kuning and Menoreh Jambon only as variety.